Pembuatan Dan Karaktrisasi Karbon Aktif Berbahan Dasar Cangkang Sawit Dengan Metode Aktivasi Fisika Menggunakan Rotary Autoclave - Ibrahim Ibrahim; Awaludin Martin; Nasruddin Nasruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Activated carbon is an absorbent that has widely used because it’s high absorption capacity. Necessity to improve the quality of activated carbon made from palm shells with low price and easy to obtain. The process of preparation and characteristics of activated carbon conducted in this research using physical activation using CO2 as the activating agent. Carbonization and activation processes performed in a rotating furnace (rotary autoclave) by flowing nitrogen gas (N2) at 100 ml/min and CO2 flow rate of 250 ml/min. Carbonization temperature 500oC was used with some variation of carbonization time, activation time and activation temperature. The results seen with activated carbon characteristics knowing iodine numbers obtained from any activated carbon produced. Optimum characteristics of activated carbon obtained by activation at 750oC temperature, the duration of carbonization and activation of activated carbon produced during 2 hours with 603 g / kg of iodine number.Keywords: Rotary Autoclave, iodine, Activated Carbon.